Application of chicken eggshell and coconut shell-based adsorbents for surfactant removal in laundry industry - Rachmawati, Siti; Agustin, Mariska Rosida; Purwono, Purwono (Journal of Water and Land Development, 2026)
*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-6a4b9991-224c-83eb-8190-d0e833776905-16" data-turn-id-container="request-6a4b9991-224c-83eb-8190-d0e833776905-16" data-testid="conversation-turn-262" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" data-conversation-screenshot-content=""> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="c016583a-b95a-4814-9816-a3ecc23b2471" data-turn-start-message="true" data-message-model-slug="gpt-5-5-thinking"> The rapid growth of laundry services industry has increased the generation of wastewater containing linear alkylbenzene sulphonate (LAS), a surfactant that poses potential risks to aquatic environments. This study aims to assess the effectiveness of eggshell and coconut shell-based adsorbents for LAS removal in laundry wastewater and to determine the composition ratio and contact time resulting in the highest reduction of LAS. This study used the batch method to assess the effectiveness of the combined adsorbent, with LAS concentrations determined using the methylene blue active substances (MBAS) method through UV-Vis spectrophotometry at 652 nm. Five adsorbent percentage mass composition ratios (100:0, 75:25, 50:50, 25:75, and 0:100) were evaluated at contact times of 60, 90, 120, and 150 min. The result indicated that the chicken eggshell and coconut shell-based adsorbent was highly effective for LAS removal in laundry wastewater, achieving a high removal efficiency of 95.35% and an adsorption capacity of 0.156 mg∙g⁻¹. Moreover, the best variation that achieved the highest reduction of LAS levels in laundry wastewater was the 50%:50% ratio of carbonised chicken eggshell to coconut shell from a total of 20 g of adsorbent, with a contact time of 120 min. This high performance was attributed to the synergistic mechanisms involving physical adsorption by carbonised coconut shell-based activated carbon through van der Waals forces and hydrophobic interactions, along with chemical adsorption by chicken eggshells via ionic interactions between Ca²⁺ ions and sulphonate (SO₃⁻) groups of LAS.